Citizen participation in local waste management - Blasa, Angelique C. (Animo Repository, 2018)
Flooding in Metro Manila is a common scenario after a short, heavy downpour, and the major cause is solid waste clogging drainage systems. Metro Manila generates the most waste in the Philippines at an average of 8.910 tons per day from 2012 to 2016. Ideally, Republic Act No. 9003, also known as the "Ecological Solid Waste Management Act of 2000," should address this growing problem at the local government unit (LGU) level. However, after seventeen years into passing, its implementation still remains a challenge.LGUs should provide durable steel trash bins that can be bolted onto sidewalks to prevent their theft. Private establishments, and local vendors should be required to provide trash bins within their vicinities. People will not liter if they have easy access to trash bins. Restaurants, convenience stores, and small eateries can also implement the "Clean as You Gp" or CLAYGO system.Aside from these efforts, changing mindsets and behaviors of individuals at all levels of the community will establish more sustainable waste management system. A survey will be conducted to explore the behavior of people towards their community waste management in Manila. It is hypothesized that the current attitudes of the residents towards waste generation and handling are leading to increasing solid waste in the Metro. The study will include: level of understanding of the society towards waste generation and management, common practices leading to large amounts of solid wastes, willingness of the people of change such practices, and motivating factors to reduce waste generation.Engaging people to participate increases effectiveness of the programs. Citizen participation can be more effective when LGUs develop and skills of the community, residents recognize their roles and responsibilities, and motivation and interaction exist among stakeholders.